Pemberdayaan Guru Madrasah Ibtidaiyah Muhammadiyah (MIM) Kertonatan dalam penyadaran tentang miskonsepsi Ilmu Pengetahuan Alam (IPA) - Anatri Desstya; Rista Ayu Sadevi; Desi Tri Wulandari (Nur Science Institute, 2026)
A misconception is a condition in which a learner’s understanding does not align with the scientific concepts established by scientists. Misconceptions in science are likely to occur because they involve many concepts. The objectives of this community service activity are to empower teachers at Madrasah Ibtidaiyah Muhammadiyah (MIM) Kertonatan to reflect on their understanding of science concepts and to ensure that teachers at Madrasah Ibtidaiyah Muhammadiyah (MIM) Kertonatan have a solid understanding of the concept of sound. This outreach method will be implemented in several stages, namely: lectures, demonstrations, and experiments. The results of this community service activity show that teachers understood the misconception regarding the pitch of sound. The community service activity successfully raised teachers’ awareness of misconceptions in science and reinforced their understanding of the correct concepts of sound through demonstrations and experiments.